2010
DOI: 10.32635/2176-9745.rbc.2010v56n1.1537
|View full text |Cite
|
Sign up to set email alerts
|

Assistência à Saúde da Criança com Câncer na Produção Científica Brasileira

Abstract: No Brasil, a partir dos dados obtidos do registro de câncer de base populacional, observou-se que câncer infantil varia de 1% a 4,6%. É uma especialidade contemporânea e tem seu corpo de conhecimento e prática em processo de construção. O objetivo da pesquisa foi mapear as produções científicas brasileiras da temática de câncer em crianças. Para tanto, foi feita a seleção dos artigos disponíveis on-line na íntegra e sua classificação, segundo as variáveis: ano, região, subárea e tipo de estudo; e a análise da … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 11 publications
0
8
0
5
Order By: Relevance
“…9,[12][13][14][15][16][17][18][19][20][21] When communication is used as a mean for exchanging information, it becomes extremely important for parents, a good conversation between nurse and family includes the way the news is given, the clarity of the treatment and the clarification of doubts peculiar to parents. [2][3][4][5][6][7][8][9] An effective communication tool is writing, one of the studies 11 reported the creation of an institutional teaching material written in a booklet format containing information explaining cancer treatment as well as its side effects and tips on what should be done when undergoing chemotherapy treatment. This instrument was considered satisfactory by the families and patients who received the booklet as a good way to understand the disease, especially when it is at the beginning of treatment, in which much new information that is completely unknown by parents comes out.…”
Section: Communication As a Mean For Guidance And Emotional Supportmentioning
confidence: 99%
See 2 more Smart Citations
“…9,[12][13][14][15][16][17][18][19][20][21] When communication is used as a mean for exchanging information, it becomes extremely important for parents, a good conversation between nurse and family includes the way the news is given, the clarity of the treatment and the clarification of doubts peculiar to parents. [2][3][4][5][6][7][8][9] An effective communication tool is writing, one of the studies 11 reported the creation of an institutional teaching material written in a booklet format containing information explaining cancer treatment as well as its side effects and tips on what should be done when undergoing chemotherapy treatment. This instrument was considered satisfactory by the families and patients who received the booklet as a good way to understand the disease, especially when it is at the beginning of treatment, in which much new information that is completely unknown by parents comes out.…”
Section: Communication As a Mean For Guidance And Emotional Supportmentioning
confidence: 99%
“…Family members' affective experience with the disease, the moment of diagnosis and the beginning of treatment are the most difficult phases. 2,3 The impact on the family is usually related to extensive and frequent periods of hospitalization, aggressive therapy, limitations in understanding the diagnosis, suffering, anguish, and pain. Thus, the nurse, as well as the entire health team needs to emotionally assist these families by enabling them so that they can orient themselves along the path of the disease, reduce the stress of hospitalization and maintain hope about the reality imposed on them.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leukemia is the most common among children under 15 years, mainly acute lymphocytic leukemia (ALL). 2 When exhaust the possibilities of curing a child with poor prognosis, we adopt palliative care aimed at relieving symptoms without curative intent providing quality of life.…”
mentioning
confidence: 99%
“…The support is from the relief of suffering by controlling pain and symptoms, as well as the psychosocial and spiritual. 2 Palliative care is a subject that requires a daily reflection, especially when you think that technology advances can increase the life expectancy of patients without therapeutic management, which may not be synonymous with quality of life. This care is aimed at the development of a natural death, showing the importance of a comprehensive care when it comes to children with leukemia.…”
mentioning
confidence: 99%